What Workers Say : Employee Voice in the Anglo-American Workplace - Haynes, Peter, 1955-; Boxall, Peter F.; Freeman, Richard B. (Richard Barry), 1943- (Book collections on Project MUSE., 2007)
This book brings together research in the United States, Canada, the United Kingdom, Ireland, Australia, and New Zealand to answer a series of key questions:* What opportunities do employees in Anglo-American workplaces have to voice their concerns and what do they seek? * To what extent, and in what contexts, do workers want greater union representation? * How do workers feel about employer-initiated channels of influence? What styles of engagement do they want with employers?* What institutional models are more successful in giving workers the voice they seek at workplaces? * What can unions, employers, and public policy makers learn from these studies of representation and influence? The research is based largely on surveys that were conducted as a follow-up to the influential Worker Representation and Participation Survey (WRPS) reported in What Workers Want, coauthored by Richard B. Freeman and Joel Rogers in 1999 and updated in 2006. Taken together, these studies authoritatively outline workers' attitudes toward, and opportunities for, representation and influence in the Anglo-American workplace. They also enhance industrial relations theory and suggest strategies for unions, employers, and public policy.